2015
DOI: 10.1002/ffj.3269
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and stability of W/O/W emulsions containing sucrose as weighting agent

Abstract: The objective of present study was to evaluate the use of sucrose as a weighting agent in W/O/W emulsions. Placing sucrose in the internal water phase could increase the density of the oil droplet and provide natural weighing to the oil phase. A 60 wt% sucrose solution with or without gelatin served as inner aqueous phase (W). Orange oil terpenes (OT) or Miglyol 812 (MCT) were compared as oil phase (O). Different concentrations of polyglycerol polyricinoleate (PGPR) were evaluated as lipophilic emulsifier. Gum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 33 publications
6
40
1
Order By: Relevance
“…In case of δ > 1, a large δ value (δ = 16.6) is required to model the SED of knot-B1. This value is comparable with the derived variability Doppler factor of δ = 17 for pc-scale jet in Hovatta et al (2009), but is much larger than that reported by Liodakis et al (2017, δ = 3.7), and even larger than the core-jet value of δ = 7.4 ± 0.9 derived by SED fitting (Zhang et al 2014(Zhang et al , 2015. Therefore, Scenario I could not present a reasonable explanation for the SEDs of knots.…”
Section: Discussionsupporting
confidence: 70%
“…In case of δ > 1, a large δ value (δ = 16.6) is required to model the SED of knot-B1. This value is comparable with the derived variability Doppler factor of δ = 17 for pc-scale jet in Hovatta et al (2009), but is much larger than that reported by Liodakis et al (2017, δ = 3.7), and even larger than the core-jet value of δ = 7.4 ± 0.9 derived by SED fitting (Zhang et al 2014(Zhang et al , 2015. Therefore, Scenario I could not present a reasonable explanation for the SEDs of knots.…”
Section: Discussionsupporting
confidence: 70%
“…The bulk Lorentz factor of the emission region is Γ, and the beaming factor should be δ = 1/Γ(1−β cos θ), where θ is the viewing angle. The radiation electron distribution is taken as a broken power-law (Ghisellini et al 2009;Zhang et al 2014Zhang et al , 2015Chen et al 2012), and this distribution is characterized by an electron density parameter (N 0 ), a break energy (γ b ) , and two slope indices (p 1 and p 2 ) below and above the break energy in the energy range of γ e ∈ [γ min , γ max ]. The Klein-Nashina (KN) effect and the absorption of high energy γ-ray photons by extragalactic background light (Franceschini et al 2008) are also taken into account in our model calculations.…”
Section: Sed Modeling and Results For The Core And Knotsmentioning
confidence: 99%
“…As illustrated in Figure 2, the blue bump of the thermal emission from the accretion disk is prominent when the source is in a low state of γ-ray radiation. Following our previous work (Sun et al 2015;Zhang et al 2015), the standard accretion disk spectrum (Davis & Laor 2011) is used to explain this thermal emission. The fitting parameters include the inside (R in ) and outside radii (R out ) of the accretion disk, black hole mass (M BH ), Eddington ratio, and inclination to the line of sight i.…”
Section: The Core Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that the adopted value of a affects the feasibility of JCIs: values of α > 1 (e.g. Zhang et al 2015) make it more likely that BLR clouds penetrate powerful jets since JCIs require that R BLR > z min (see Eq. 1 and Sect.…”
Section: Broad-line Regionmentioning
confidence: 99%